Burnout in Family Doctors from a Portuguese Region in Relation to the COVID-19 Pandemic - Camões, Ana Catarina; Melo Ferreira, Maria Inês; Fróis, Ana Teresa; Silva, José Caetano; Costa, Cassilda; Correia, Raquel S.; Ferreira, Fátima (Gazeta Médica, 2022)
INTRODUCTION: During the COVID-19 pandemic, burnout cases appear to have worsened within physicians. This study aimed at determining the prevalence of burnout, reflecting the COVID-19 pandemic, in family physicians from a region in Portugal. MATERIAL AND METHODS: Analytical cross-sectional study with a self-administered online questionnaire, during april and march of 2021. Application of Maslach Burnout Inventory-Health Services Survey. RESULTS: 60 valid responses were obtained, with a mainly feminine (82%) sample, between 36 and 45 years of age (53%). A total of 52% claimed to have thought of changing jobs, institution, or service in the past month. A percentage of 70% presented high emotional exhaustion, 40% high depersonalization, and 45% low personal realization. Suffered from burnout 32%. Emotional exhaustion was higher for those with weekly schedule above 40 hours (p=0.011). Low personal realization (p=0.004) and burnout (p=0.034) were more prevalent in the lower age groups. There were no significant relations between burnout and sex or place of work. DISCUSSION: Burnout estimated prevalence in family physicians is twice that of 2016 in the north of Portugal and eight times that of 2012 nationwide. Given the temporal relationship, there is probably a relation between this rise in prevalence and the COVID-19 pandemic. The higher prevalence of burnout in the younger physicians may be due to less effective coping strategies against work stress. CONCLUSION: Burnout prevention should be a priority within family physicians, given its high prevalence and impact on mental health, as well as being a form of quinquinary prevention in health.